Amino acid profile in Down's syndrome. Issue 4 (April 1996) - Heggarty, H J; Ball, R; Smith, M; Henderson, M J
Abstract : Fasting plasma and urinary amino acid concentrations were studied under carefully controlled conditions in 22 children with Down's syndrome and in age matched controls. The only significant difference between the groups was a higher mean plasma lysine concentration in Down's syndrome patients compared to controls.